Linguistic interaction between spanish and mapudungun in a rural bilingual community (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This research exposes the sociolinguistic contact between mapudungun and Spanish of Chile inside of a bilingual rural community mapuche/spanish. We review the linguistic interaction between both codes in sociolinguistics domains related with the intergenerational transmission, the sociolinguistic domains and the communicative events. The information has been extracted from a sociolinguistic questionnaire applied to 20 people living in the lafkenche area of Isla Huapi. The collected data allows us to describe the interactive processes between the codes and to predict the formation of a different type of Spanish spoken in these communities. All of this occurs under the framework suggested by Godenzzi (2007) who validates the formation of particular language varieties, which are created in situations of historical sociolinguistic conflicts characterized by dynamics of opposition and complementarity.
Keywords: Linguistic interaction; sociolinguistics domains; transmission; language sociology